2023
DOI: 10.1007/s12672-023-00641-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between response to anti-PD-1 treatment and blood soluble PD-L1 and IL-8 changes in patients with NSCLC

Abstract: In this study, we explored the dynamic changes in blood sPD-L1 and its clinical value during anti-PD-1 immunotherapy in non-small cell lung cancer (NSCLC) patients. First, we established a sandwich ELISA for functional sPD-L1 that can bind to PD-1 and has biological functions. By monitoring functional sPD-L1 in 39 NSCLC patients treated with anti-PD-1 antibodies, we found a positive correlation between baseline sPD-L1 and tissue PD-L1 (P = 0.0376, r = 0.3581), with patients with lymph node metastasis having hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Their study indicates that observing changes in sPD-L1 levels and IL-8 can offer valuable information on the patient's response to treatment. This technique can serve as a valuable tool in evaluating the effectiveness of anti-PD-1 immunotherapy in NSCLC patients [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their study indicates that observing changes in sPD-L1 levels and IL-8 can offer valuable information on the patient's response to treatment. This technique can serve as a valuable tool in evaluating the effectiveness of anti-PD-1 immunotherapy in NSCLC patients [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have indicated that interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) have different expressions in PCa tissues [14][15][16]. Another study found that interleukin-8 (IL-8) is also expressed in various cancers such as gastric cancer, esophageal cancer, and lung cancer to varying degrees [17][18][19][20]. Additionally, the remaining relevant reports include interleukin-2(IL-2), interleukin-4(IL-4), interleukin-5(IL-50), Interferonα(IFN-α), Interferon-γ(IFN-γ), Interleukin-1β(IL-1β), and Interleukin-12p70(IL-12p70), all of which also associated with the occurrence and development of prostate disorders.…”
Section: Introductionmentioning
confidence: 99%